دور الثقافة التنظمية في تشكيل هوية مهنية لدى أستاذة التعليم العالي - علي قعري; حمزه بلال (جامعة الوادي - University of Eloued, 2025)
"‏ تناولت دراستنا هذه دور الثقافة التنظيمية في تشكيل الهوية المهنية لدى أساتذة التعليم العالي، من خلال دراسة ‏ميدانية بكلية العلوم الإنسانية والاجتماعية بجامعة الوادي، حيث هدفت إلى الكشف عن أثر القيم والعادات ‏والممارسات التنظيمية السائدة في تعزيز أو إضعاف شعور الأستاذ الجامعي بالانتماء والهوية المهنية، ومن هنا أظهرت ‏النتائج أن هناك وجود لمناخ تنظيمي إيجابي يقوم على الثقة والتقدير والدعم الإداري، يساهم في ترسيخ هوية مهنية قوية، ‏كما بينت أن غياب العدالة والتواصل الفعال داخل المؤسسة يؤثر سلبا على الانخراط المهني ويضعف الأداء، ثم خلصت ‏الدراسة إلى أهمية تطوير ثقافة تنظيمية محفزة تدعم بدورها الاحترام المتبادل وتعزز من الاستقرار والتطور المهني للأستاذ.‏ "‏ ‏This study addressed the role of organizational culture in shaping the ‎professional identity of higher education faculty members, through a field ‎study conducted at the Faculty of Social and Human Sciences at the ‎University of El Oued. The aim was to uncover the impact of prevailing ‎organizational values, customs, and practices on strengthening or ‎weakening university professors’ sense of belonging and professional ‎identity. The findings revealed the presence of a positive organizational ‎climate based on trust, appreciation, and administrative support, which ‎contributes to establishing a strong professional identity. The study also ‎showed that the absence of justice and effective communication within ‎the institution negatively affects professional engagement and weakens ‎performance. It concluded by emphasizing the importance of developing ‎a motivating organizational culture that fosters mutual respect and ‎enhances the professional stability and development of faculty members.‎ K"
مذكرة ماستر قسم علوم الاجتماعية تخصص علم اجتماع تنظيم وعمل
Keywords: الثقافة التنظيمية; الهوية المهنية; أساتذة التعليم العالي; جامعة الوادي; كلية العلوم الإنسانية ‏والاجتماعية; eywords: Organizational culture; professional identity; higher education faculty; ‎University of El Oued; Faculty of Social and Human Sciences.‎